Impact of Lactational Exposure to Polychlorinated Biphenyl Causes Epigenetic Modification and Impairs Sertoli Cells Functional Regulators in F1 Progeny. (June 2018) - Priya, E. Sugantha; Kumar, T. Sathish; Singh, P. Raja; Balakrishnan, S.; Arunakaran, J.
Polychlorinated biphenyl (PCB) is an endocrine-disrupting chemical. Sertoli cells (SCs) provide physical and nutritional support for developing germ cells. Dysfunction in SCs has adverse effects on spermatogenesis. Previously, we found that the lactational exposure of PCBs (1, 2, and 5 mg/kg birth weight/day, orally from postnatal days 1 to 20) decreased the follicle-stimulating hormone receptor (FSHR) and androgen receptor (AR) expression in SCs of F1 progeny. Transcription factors initiate and regulate the transcription of genes. DNA methylation plays an important role in epigenetic gene regulation. Hence, this study was aimed to identify the level of transcription factors regulating FSHR, AR gene expression, and DNA methylation in the promoter of these genes in SCs of both F1 prepuberal and puberal offspring. DNA methylation in the promoter of FSHR and AR genes was examined by sodium bisulfite conversion technique. The protein levels of transcription factors (steroidogenic factor 1 [SF1], upstream stimulatory factors 1 and 2, c-fos, c-jun, and CREB-binding protein) and enzymes DNA methyltransferases (Dnmt1, Dnmt3ab, Dnmt3l, and histone deacetylase 1 [HDAC1]) were analyzed by Western blotting. The transcription factors that regulate the FSHR and AR gene in SCs were decreased in both the PCB-exposed F1 progeny. Methylation was observed in the promoter of FSHR, AR, and SF1. The protein levels of Dnmt1, Dnmt3ab, Dnmt3l, and HDAC1 were increased in the PCBs-treated groups. Subsequently, it leads to transcriptional repression of the genes in SCs. Our finding suggests that PCBs caused epigenetic change in SCs, thereby it impaired SCs function in F1 progeny.